Developmental Differences in the Recognition of Facial Expressions of Emotions - López-Morales, Hernán (2021)
This research aimed to characterize the recognition of basic emotions in facial expressions in children and adolescents. A digital adaptation of theÂ Pictures of Facial AffectsÂ test was administered to 147 participants of both sexes, between 9 and 18 years old. Results showed a negative association between age and rate of success in recognition of joy, and a positive association between age and rate of success in recognition of disgust and fear. A significant effect of age on the recognition of all emotions except fear was found regarding reaction times. These results suggest that as age increases, emotional recognition is faster. However, this is not reflected in an improvement in emotional recognition. The only cases in which recognition was enhanced with age were disgust and fear. The importance of these emotions for adolescence is discussed.